The Writers that Came in from the Cold: Translator’s Visibility in the Nordic Noir Crime Fiction Published in Spain - Echauri Galván, Bruno; Roca, Alicia Camelia (TRANS: Revista de Traductología, 2025)
Nordic Noir crime fiction has become a literary phenomenon in Spain, fueled by an ever-growing influx of translations that introduce Scandinavian traditions to Spanish readers. This study examines the paratextual visibility of translators within this subgenre across publishers, critics, and readers. To this end, we analyze the peritexts of 70 translated novels and epitextual elements such as reviews, interviews, and videos. Results reveal a striking invisibility of translators: their names are mostly confined to copyright pages and rarely appear on covers or in authored peritexts. Similarly, epitexts seldom feature translators, with rare mentions in articles or comments on target texts. This marginalization highlights the limited recognition translators receive in the publishing industry and critical discourse. It also reflects a symbolic capital in the red plus a troubling undervaluation of their crucial role in literary circulation and in driving the Nordic Noir boom that has shattered sales records in Spain.